IN-VITRO EVALUATION OF ANTI-TRICHOMONAL ACTIVITIES OF EUGENIA UNIFLORA LEAF. - ADEBAJO, Adeleke Clement; Ibikunle, Gabriel Femi; Famuyiwa, Funmilayo Gladys; Aladesanmi, Adetunji Joseph; Adewunmi, Clement Oladapo (African Journal of Traditional, Complementary and Alternative Medicines, 2010)
Eugenia uniflora, used ethnomedically in some tropical countries as an anti-infective, has shown anti-malarial and anti-trypanocidal activities. Therefore using bioactivity guided fractionation, anti-trichomonal activity of E. uniflora leaf was investigated. Anti-trichomonal activities of leaf methanol extract and its fractions against Trichomonas gallinae as well as their cytotoxicities using an in vitro haemaglutination assay were determined. Anti-trichomonacidal activities of the extract improved on purification up to a stage. Subfractions E2-5 had LC50 and LC90 values of 4.77 - 5.28, 18.49 - 25.00 and 4.53 - 5.18, 18.32 - 19.07 Î¼g/ml at 24 and 48 hrs, respectively that were better than those of metronidazole. Further purification of E2-5 led to loss of activity suggesting that the active components were probably working synergistically and additively. Demonstration of low haemaglutination titre values of 0.00 – 5.33 by methanolic extract and its partition fractions suggested their low toxicity profile. The established safety of the leaf indicated that its anti-trichomonal activity was not due to non-specific cytotoxicity, hence could be used in ethnomedicine as an anti-trichomonal agent.